BIOMARCADORES SATURADOS EM ÓLEOS DA BACIA SERGIPE-ALAGOAS BRASIL: DISTRIBUIÇÃO E CONCENTRAÇÃO - Lima, D. I.; Lima, S. F.; Silva, V. V.; Sant´Ana, A. E. G.; Rebouças, L. M. C. (Geochimica Brasiliensis, 2012)